Instancija lirskoga subjekta i hrvatska petrarkistička lirika - Bogdan, Tomislav (Array, 2001)
The basic tenets of the theory of the lyrical subject are illustrated on examples from Croatian Petrarchistic poetry. The lyrical subject is hereby defined strictly as a textual subjectivity, the highest instance of utterance, i.e. as a non-narrative analogue to the narrator in a narrative. In the course of the study of the lyrical subject, certain narratological insights have been applied, and the history of the usage of this and similar concepts has been discussed as well. Proceeding from the analysis of the elements of the intratextual communication structure, a description of the lyrical subject’s status has proved appropriate for various typological classifications of Petrarchistic poetry.